Atherosclerotic Cardiovascular Disease Risk and Lipid-Lowering Therapy Requirement in China - Bi, Lei; Yi, Jiayi; Wu, Chaoqun; Hu, Shuang; Zhang, Xingyi; Lu, Jiapeng; Liu, Jiamin; Zhang, Haibo; Yang, Yang; Cui, Jianlan; Xu, Wei; Song, Lijuan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Lipid-lowering therapy (LLT) is one of the key strategies for reducing the atherosclerotic cardiovascular disease (ASCVD) burden. However, little is known about the percentage of people in need of different LLT regimens to achieve optimal targets of low-density lipoprotein cholesterol (LDL-C), and the corresponding cost and benefit. Methods We conducted a simulation study based on the data from the nationwide China PEACE MPP population cohort (2015–2020), from which we included 2 904 914 participants aged 35–75 years from all the 31 provinces in mainland China. Participants were grouped based on their 10-year ASCVD risks, then entered into a Monte Carlo model which was used to perform LLT intensification simulation scenarios to achieve corresponding LDL-C goals in each risk stratification. Results After standardizing age and sex, the proportions of participants included at low, moderate, high, and very-high risk were 70.8%, 15.6%, 11.5%, and 2.1%, respectively. People who failed to achieve the corresponding LDL-C goals – 8.1% at low risk, 19.6% at moderate risk, 53.2% at high risk, and 93.6% at very-high risk (either not achieving the goal or not receiving LLT) – would be in need of the LLT intensification simulation. After the use of atorvastatin 20 mg was simulated, over 99% of the population at low or moderate risk could achieve the LDL-C goals; while 11.3% at high and 24.5% at very-high risk would still require additional non-statin therapy. After the additional use of ezetimibe, there were still 4.8% at high risk and 11.3% at very-high risk in need of evolocumab; and 99% of these two groups could achieve the LDL-C goals after the use of evolocumab. Such LLT intensification with statin, ezetimibe, and evolocumab would annually cost 2.4 billion, 4.2 billion, and 24.5 billion, respectively, and prevent 264 170, 18 390, and 17 045 cardiovascular events, respectively. Conclusions Moderate-intensity statin therapy is pivotal for the attainment of optimal LDL-C goals in China, and around 10-25% of high- or very-high-risk patients would require additional non-statin agents. There is an opportunity to reduce the rising ASCVD burden in China by optimizing LLT.